Evaluation of the Level of Roughness of West Papua National Roads Using Roughometer III: Case Study: Roads in Manokwari City (JISTECH: Journal of Information Science and Technology, 2024)
Road is one of the important and influential transportation infrastructures for the development of an area.  This development will affect the volume of traffic which will put an increasing load on the pavement so that this has an impact on the functional decline of the road.  The functional management of  the road  becomes a measure in  the assessment which becomes a reference for determining the type of evaluation program that must be carried out, one of which is road roughness. In this study, the evaluation of the level of road leveling using  the International roughness index (IRI)  method as an indicator in the assessment ofan roads produced from the Roughometer III tool.  Evaluation is carried  out to determine  the unevenness of road sections and  road  handling carried out for the level of road damage. From the calculation results, it is known that the condition   of the level of equality on the ruas of the Yos Sudarso Manokwari road L line (left), 76.53% Good, 23.47% Fair, and R lane (right), 4.69% Excellent,   67.14% Good,   23.47% Fair, 4.69   % Poor .  For ruas road Trikora Wosi Manokwari  line L (left), 58.63% Good, 41.37%, and  line R (right),  3.66% Excellent, 74.35% Good, 18.32% Fair, 3.66% Poo.  On  the Drs. Esau Sesa Manokwari road section  L line (left), 3.66%  Excellent, 7.68% Good, 63.97% Fair, 25.79%  Poor 2.56%  Bad and R lane (right), 13.00%  Good     , 76.77% Fair  , 10.24% Poor